In silico analysis of plant biomass-degrading genes and thermostable enzymes from a Malaysian hot spring microbiome using targeted metagenomic approach / Lee Li Sin - Lee , Li Sin (2018)
Biomass decomposition using thermophilic enzymes has attracted attention due to their high reaction speed, thermostability, and decreased risk of contamination. Exploitation of efficient thermostable glycoside hydrolases (GHs) and auxiliary activities (AA) enzymes could accelerate the industrialisation of biofuels and biochemicals. Yet, the full spectrum of thermophiles and their enzymes that are important for biomass degradation at high temperatures are not well studied. In this work, a Malaysian hot spring located within a wooded area with fallen foliage which formed a thick layer of biomass bed under heated water represents a good resource for the discovery of microbial biomass decay communities. Here, the hypervariable regions of bacterial and archaeal 16S rRNA genes were sequenced on Illumina MiSeq platform using total community DNA extracted from the hot spring. Data suggested that 25 phyla, 58 classes, 110 orders, 171 families, and 328 genera inhabited this hot spring. Members of the genera Acidimicrobium, Aeropyrum, Caldilinea, Caldisphaera, Chloracidobacterium, Chloroflexus, Desulfurobacterium, Fervidobacterium, Geobacillus, Meiothermus, Melioribacter, Methanothermococcus, Methanotorris, Roseiflexus, Thermoanaerobacter, Thermoanaerobacterium, Thermoanaerobaculum, and Thermosipho were among the main thermophiles which harbour various GHs that may be involved in cellulose and hemicellulose breakdown. Among these communities, a variety of previously under-studied genera was found, revealing substantial diversity in foliage-rich hot springs.